Comparison of Single-Incision Scrotal Orchiopexy and Traditional Two-Incision Inguinal Orchiopexy for Primary Palpable Undescended Testis in Children: A Systematic Review and Meta-Analysis - Yu, Chengjun; Hu, Yang; Wang, Ling; Kang, Lian; Zhao, Jie; Lu, Jiandong; Lin, Tao; He, Dawei; Wu, Shengde; Wei, Guanghui (Frontiers in Pediatrics, 2022)
Purpose: To compare the safety, efficacy, and cosmetic results of single incision scrotal orchiopexy (SISO) and traditional two-incision inguinal orchiopexy (TTIO) for primary palpable undescended testes (PUDT) in children. Materials and Methods: A systematic literature search of all relevant studies published on PubMed, Embase, Medline, Cochrane library, Web of Science database, and Wanfang data until July 2021 was conducted. The operative time, hospitalization duration, conversion rate, wound infection or dehiscence, scrotal hematoma or swelling, testicular atrophy, re-ascent, hernia or hydrocele, analgesics needs, and cosmetic results were compared between SISO and TTIO using the Mantel–Haenszel or Inverse Variance method. Results: A total of 17 studies involving 2627 children (1362 SISO and 1265 TTIO) included in final analysis. The conversion rate of SISO was 3.6%. The SISO approach had a statistically significant shorter operative time than the TTIO approach for PUDT (WMD –11.96, 95% CI –14.33 to –9.59, I2 = 79%, P ＜0.00001), and a shorter hospital stay (WMD –1.05, 95% CI –2.07 to –0.03, P = 0.04). SISO needed less analgesics and had better cosmetic results than TTIO. SISO had similar total, short-term, or long-term complication rate with TTIO. Conclusions: Compared with TTIO, SISO has the advantages of shorter operative time, shorter hospitalization duration, less postoperative pain, and better cosmetic appealing results. SISO is a safe, effective, promising, and potential minimal invasive surgical approach for PUDT. SISO is an alternative to TTIO in selected cryptorchid patients, especially for lower positioned ones.